2021
DOI: 10.3390/molecules26154536
|View full text |Cite
|
Sign up to set email alerts
|

Setup of an Ultrasonic-Assisted Extraction to Obtain High Phenolic Recovery in Crataegus monogyna Leaves

Abstract: Hawthorn leaves are a rich source of phenolic compounds that possess beneficial activities for human health. Ultrasonic-assisted extraction (UAE) is an extraction technique frequently used for the isolation of phenolic compounds in plants. Thus, in this study, a Box–Behnken design was used to optimize UAE conditions such as the percentage of acetone, the extraction time and solvent-to-solid ratio (v/w) in order to obtain the maximum content of total compounds by Folin–Ciocalteu and the maximum in vitro antioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Various techniques are currently in use, such as: maceration, Soxhlet extraction, supercritical extraction, microwave-assisted extraction, pulsed electric field assisted extraction, and high pressure solvent extraction [15][16][17][18]. Ultrasound assisted extraction (UAE) has also been commonly applied [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Various techniques are currently in use, such as: maceration, Soxhlet extraction, supercritical extraction, microwave-assisted extraction, pulsed electric field assisted extraction, and high pressure solvent extraction [15][16][17][18]. Ultrasound assisted extraction (UAE) has also been commonly applied [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the hydroalcoholic extract of C. orientalis, which had ≈314 mg total antioxidant content per g showed three times more potent antioxidant effects compared to the methanolic extract in the previous study. Martín-Garcia et al [ 36 ] investigated the DPPH radical scavenging activity of 15 different extracts prepared by varying the acetone–water ratio of C. monogyna leaves extract. The values they found ranged from ≈38 to 101 mg TE/g extract.…”
Section: Discussionmentioning
confidence: 99%
“…Each experiment was carried out in duplicate. The independent variables were time (5,45, and 85 min), ratio ethanol/water (0, 50, and 100% v/v), and ratio solvent/sample (10, 105, and 200 v/w) and the dependent variable considered the total phenolic content measured by the Folin-Ciocalteu method. It was adjusted to a second-order polynomial model equation and ANOVA was performed to evaluate the adjustment of the model.…”
Section: Experimental Designmentioning
confidence: 99%
“…Furthermore, recently, there has been an increment in the demand for extracting techniques that reduce extraction times and consumption of organic solvents. Therefore, among other extraction methods, ultrasound-assisted extraction is considered an excellent green alternative that has been widely used for the extraction of phenolic compounds in other matrices [4,5]. Some authors have reported using ultrasound technology in pepper matrices but with different approaches such as for extracting hydroxy-sanshool compounds [6], capsaicinoids [7][8][9][10][11][12], capsinoids [13], β-cyclodextrin [14], minerals (Ca, Fe, K, Mg, Mn, P, and Zn) [15], oils [16], oleoresin [17], or alkenylbenzenes [18], or with other uses such as for removing the residual solvent from fragrant oils [19] or for improving drying kinetics [20][21][22].…”
Section: Introductionmentioning
confidence: 99%